2011
DOI: 10.1007/s00535-011-0399-5
|View full text |Cite
|
Sign up to set email alerts
|

EUS elastography combined with the strain ratio of tissue elasticity for diagnosis of solid pancreatic masses

Abstract: Endoscopic ultrasound elastography is a promising diagnostic tool for defining the tissue characteristics of pancreatic masses. In addition, semiquantitative analysis of elasticity using the SR may allow the differentiation of MFP from PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 22 publications
4
97
3
6
Order By: Relevance
“…First, the disease concept of NETs disseminated among general clinicians; that is, clinicians have become accustomed to keeping PNETs in mind when treating pancreatic tumors. Second, the availability of endoscopic ultrasonography (EUS), which is useful for the diagnosis of pancreatic diseases [9,10], has made endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) easy to perform for pancreatic tumors, which were merely being followed-up before; thus, the pathological diagnosis of PNETs has become more accurate [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…First, the disease concept of NETs disseminated among general clinicians; that is, clinicians have become accustomed to keeping PNETs in mind when treating pancreatic tumors. Second, the availability of endoscopic ultrasonography (EUS), which is useful for the diagnosis of pancreatic diseases [9,10], has made endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) easy to perform for pancreatic tumors, which were merely being followed-up before; thus, the pathological diagnosis of PNETs has become more accurate [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Itokawa et al (27) introduced the concept of strain ratio (SR) as a semiquantitative method to objectively evaluate tissue hardness, which is simply the ratio of the distortions produced by a force on two adjacent areas. In 2013, Iglesias-García et al (23) obtained a diagnostic accuracy of 91.1% by EUSelastography using the SR for CP with a cut-off of 2.25, describing a direct correlation between the SR and the different stages of CP according to the Rosemont classification.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus where to set reference area for the pancreas instead of fat around the mammary gland for the breast. Some investigators set reference area on non tumorous area inside pancreatic parenchyma [33,34] , and the other investigators set reference area on red area around the pancreas which was estimated as fat [35,36] (Figure 4) . However, there is no evidence if red area around pancreas is really fat.…”
Section: Us-elastography -Shear Wave Elastograhymentioning
confidence: 99%
“…Itokawa et al [34] subjected 72 ductal adenocar cinomas and 7 tumor forming pancreatitis, and reported that strain ratio was significantly higher in ductal adenocarcinomas compared to that in tumor forming pancreatitis (39.08 ± 20.54 vs 23.66 ± 12.65, P < 0.05). Iglesias Garcia et al [35] subjected 86 pancreatic tumors including 49 ductal adenocarcinomas, 27 tumor forming pancreatitis, 6 endocrine carcinomas, and 2 metastatic carcinomas.…”
Section: Eus-elastography -Strain Elastographymentioning
confidence: 99%